Multi‐Rotor Systems: Can They Increase Economy‐Wide Benefits Compared to Traditional Designs? - Jack Williamson; Kevin Connolly; Grant Allan (Wind Energy)
ABSTRACT This short communication reports on the economic consequences of increasing the market share of potentially lower‐cost offshore wind designs. We use data on the projected levelised cost of energy (LCOE) for traditional horizontal axis wind turbine (HAWT) designs compared with an illustrative multi‐rotor system which could have lower costs. Relative cost reductions are then introduced as improvements in productivity within the offshore wind generation sector in a computable general equilibrium model, exploring the economy‐wide impacts of different market share scenarios. We find that, due to its potentially lower LCOE, increasing the share of multi‐rotor designs in the United Kingdom would produce positive macroeconomic impacts, in terms of GDP and employment. Our findings suggest that there is merit in considering multi‐rotor wind systems as part of a future energy strategy, and a methodology by which the economic outcomes of any potentially lower‐cost technologies might be demonstrated.